DINAMIKA PSIKOLOGI PERKEMBANGAN PADA FASE PERKEMBANGAN MANUSIA DI DESA MULARAWI - Anggie Pitaloka Munthe; Junita Novita Butarbutar; Cinta Rusmauli Simanjuntak; Christoper Agner Sipayung; Fernidia Siburian; Dorlan Naibaho (CV. Denasya Smart Publisher, 2024)
This research examines the dynamics of developmental psychology at various stages of human life, from childhood to old adulthood. The main aim of this research is to understand the interaction and influence of biological, environmental and social factors on individual psychological development. The research results show that each stage of development has unique characteristics which are influenced by a combination of genetics, parenting patterns, education and social interactions. For example, childhood is characterized by rapid cognitive development and ongoing emotional formation, while adolescence is characterized by the development of identity and independence. In early adulthood, the primary focus is career and interpersonal relationships, whereas middle adulthood is often encompassed by self-reflection and adjustment to life changes. Ultimately, older adulthood faces the challenges of physical and psychological decline as well as the need for meaning and self-acceptance. This research emphasizes the importance of a holistic approach in understanding developmental psychology and its essence for effective psychological interventions.